The Role of Parent Engagement in Overcoming Barriers to Care for Youth Returning Home after Incarceration - Barnert, Elizabeth S. (J Community Health, 2020)
PURPOSE: To understand the role of parent engagement in overcoming barriers to care for youth re-entering the community following incarceration. METHODS: For this mixed methods study, we conducted quantitative surveys on healthcare needs and access with youth (n= 50) at 1-month post-incarceration, and semi-structured interviews with a subset of these youth (n= 27) and their parents (n= 34) at 1, 3, and 6-months post-incarceration (total 94 interviews). Differences by race/ethnicity and gender were assessed using chi-square test of proportions. We performed thematic analysis of interview transcripts to examine the role of parent engagement in influencing youths’ access to healthcare during reentry. RESULTS: Most youth were from racial/ethnic minority groups and reported multiple ACEs. Girls, compared to boys, had higher ACE scores (p=0.03), lower family connectedness (p=0.03), and worse general health (p=0.02). Youth-identified barriers to care were often parent-dependent and included lack of: affordable care (22%), transportation (16%), and accompaniment to health visits (14%). Two major themes emerged from the qualitative interviews: 1) parents motivate youth to seek healthcare during reentry and 2) parents facilitate the process of youth seeking healthcare during reentry. CONCLUSIONS: Parents are instrumental in linking youth to healthcare during reentry, dispelling prevailing myths that parents of incarcerated youth are inattentive and that youth do not want their help. Efforts that support and enhance parent engagement in access to care during reentry, such as by actively involving parents in pre-release healthcare planning, may create stronger linkages to care.